Treatment with the nitric oxide synthase inhibitor L-NAME provides a survival advantage in a mouse model of Kras mutation-positive, non-small cell lung cancer - Pershing, Nicole L.K. (Oncotarget, 2016)
Oncogenic mutations in the gene KRAS are commonly detected in non-small cell lung cancer (NSCLC). This disease is inherently difficult to treat, and combinations involving platinum-based drugs remain the therapeutic mainstay. In terms of novel, pharmacologically actionable targets, nitric oxide synthases (NOS) have been implicated in the etiology of KRAS-driven cancers, including lung cancer, and small molecular weight NOS inhibitors have been developed for the treatment of other diseases. Thus, we evaluated the anti-neoplastic activity of the oral NOS inhibitor L-NAME in a randomized preclinical trial using a genetically engineered mouse model of Kras and p53 mutation-positive NSCLC. We report here that L-NAME decreased lung tumor growth in vivo, as assessed by sequential radiological imaging, and provided a survival advantage, perhaps the most difficult clinical parameter to improve upon. Moreover, L-NAME enhanced the therapeutic benefit afforded by carboplatin chemotherapy, provided it was administered as maintenance therapy after carboplatin. Collectively, these results support the clinical evaluation of L-NAME for the treatment of KRAS mutation-positive NSCLC.